Influence of high altitude on cerebral blood flow and fuel utilization during exercise and recovery. (15th December 2014) - Smith, K. J.; MacLeod, D.; Willie, C. K.; Lewis, N. C. S.; Hoiland, R. L.; Ikeda, K.; Tymko, M. M.; Donnelly, J.; Day, T. A.; MacLeod, N.; Lucas, S. J. E.; Ainslie, P. N.
Abstract : Key points: This study assessed the dynamic response of global cerebral blood flow (CBF) and cerebral fuel utilization during and following incremental supine exercise to exhaustion. Global CBF increased more during exercise and recovery at high altitude (HA) compared with sea level (SL) such that cerebral oxygen delivery ( C D O 2 ) was maintained. The increase in cerebral metabolic rate of oxygen during maximal exercise at HA was half the increase observed at SL. Arterial lactate production during exercise at the same absolute intensities was greater at HA compared with SL, but reduced at the same relative intensities. Cerebral carbohydrate uptake (lactate and glucose) is greater than oxygen uptake at HA compared with SL, indicating a shift towards an increased non‐oxidative metabolic utilization. These results suggest that CBF increases to maintain C D O 2 during exercise at HA while changes in arterial lactate concentration and exercise intensity augment the oxidative and non‐oxidative pathways to cerebral metabolism at HA. Abstract: We examined the hypotheses that: (1) during incremental exercise and recovery following 4–6 days at high altitude (HA) global cerebral blood flow (gCBF) increases to preserve cerebral oxygen delivery ( C D O 2 ) in excess of that required by an increasing cerebral metabolic rate of oxygen ( CM R O 2 ); (2) the trans‐cerebral exchange of oxygen vs . carbohydrates (OCI; carbohydrates = glucose + ½lactate) would be similar during exercise and recovery at HA and sea level (SL). Global CBF, intra‐cranial arterial blood velocities, extra‐cranial blood flows, and arterial–jugular venous substrate differences were measured during progressive steady‐state exercise (20, 40, 60, 80, 100% maximum workload ( W max )) and through 30 min of recovery. Measurements ( n  = 8) were made at SL and following partial acclimatization to 5050 m. At HA, absolute W max was reduced by ∼50%. During submaximal exercise workloads (20–60% W max ), despite an elevated absolute gCBF (∼20%, P  < 0.05) the relative increases in gCBF were not different at HA and SL. In contrast, gCBF was elevated at HA compared with SL during 80 and 100% W max and recovery. Notwithstanding a maintained C D O 2 and elevated absolute CM R O 2 at HA compared with SL, the relative increase in CM R O 2 was similar during 20–80% W max but half that of the SL response (i.e. 17  vs . 27%; P  < 0.05  vs . SL) at 100% W max . The OCI was reduced at HA compared with SL during 20, 40, and 60% W max but comparable at 80 and 100% W max . At HA, OCI returned almost immediately to baseline values during recovery, whereas at SL it remained below baseline. In conclusion, the elevations in gCBF during exercise and recovery at HA serve to maintain C D O 2 . Despite adequate C D O 2 at HA the brain appears to increase non‐oxidative metabolism during exercise and recovery.